(untitled) (Damascus University Journal of educational and Psychologyical sciences, 2024)
The aim of this research is to determine the degree of employment of knowledge management processes in scientific research among graduate students in the College of Education at the Universities of Damascus and Tishreen, and the effect of variables (university, degree, gender, number of published research) in that, and in order to achieve the objectives of the research the method was used The descriptive questionnaire consisted of (16) phrases distributed among the four knowledge management processes, and the research sample consisted of (71) male and female graduate students enrolled in the thesis stage at the Faculty of Education at the Universities of Damascus and Tishreen, and the research reached the following results. : The degree of employing the processes of organizing and storing knowledge, and exchanging and disseminating knowledge in scientific research among graduate students at the Faculty of Education at Damascus and Tishreen Universities was high. The degree of employing the two processes of knowledge generation and the use of knowledge in scientific research among graduate students in the Faculty of Education at Damascus and Tishreen Universities was medium. There are statistically significant differences in the degree of employment of knowledge management processes in scientific research among graduate students in the College of Education at Damascus and Tishreen Universities. According to the variable of the university in favor of the students of Damascus University, and according to the variable of the study stage in favor of doctoral students, and according to the variable of the number of published researches in favor of the students who published more than two research papers.